Psychological care reflecting the specifics of the course of viral infection in SARS-CoV-2 oncological patients with oxygenation disorder - a case series - Skřivanová, K; Smetana, Jr K; Korbička, T; Hudec, J; Jaborník, M; Procházka, V (Klinicka onkologie, 2023)
BACKGROUND: During the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic, patients treated with acute coronavirus disease 2019 (COVID-19) in intensive care units (ICU) have suffered from neuropsychiatric complications such as anxiety, depression, and confusion. Conditions related to the environment have the potential to worsen these symptoms. In combination with virus-dependent neuroinflammation, they form a "toxic" mixture. Discussion and planning strategies for providing psychological care in the ICU during the pandemic have revealed a great current challenge. CASE SERIES: We share our experience concerning psychological interventions for oncological patients with oxygen saturation depletion. Our observation of two SARS-CoV-2 patients suggests a close time-related association between the increase in inflammatory markers interleukin 6 (IL-6) and C-reactive protein (CRP) and intensive anxiety in the fast development of breath shortening in acute COVID-19 infection due to brain hypoxia and potential neuroinflammation. CONCLUSION: As cytokine IL-6 regulates induction of CRP gene expression, the changes in IL-6 concentrations associated with anxiety symptoms and breath shortening in the observed cluster can be detected hours earlier than changes in CRP levels, with a diagnostic implication for the clinicians. The SARS-CoV-2 patients with oncological diseases treated in our ICU asked for personal bedside contact with clinical psychologists, considered it irreplaceable and reported this psychological care as beneficial.
Keywords: psychological care; neurozánětlivé nemoci; Neuroinflammatory Diseases; Interleukin-6; COVID-19; Intensive Care Units; Humans; anxiety; brain hypoxia; SARS-CoV-2; C-reactive protein– neuroinflammation; lidé; jednotky intenzivní péče; interleukin-6; anxiety– interleukin 6; intensive care unit